2020
DOI: 10.1186/s13568-020-01047-x
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial mechanism of rhodomyrtone involves the disruption of nucleoid segregation checkpoint in Streptococcus suis

Abstract: Rhodomyrtone has been recently demonstrated to possess a novel antibiotic mechanism of action against Grampositive bacteria which involved the multiple targets, resulting in the interference of several bacterial biological processes including the cell division. The present study aims to closely look at the downstream effect of rhodomyrtone treatment on nucleoid segregation in Streptococcus suis, an important zoonotic pathogen. The minimum inhibition concentration (MIC) and the minimum bactericidal concentratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Rhodomyrtone also causes the release of ATP and cytoplasmic proteins which can interfere with the metabolic processes of bacterial cells. However, it is not known for sure how the direct effect of rhodomyrtone in the process of structural and physical cell changes that occur in bacteria (Traithan et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Rhodomyrtone also causes the release of ATP and cytoplasmic proteins which can interfere with the metabolic processes of bacterial cells. However, it is not known for sure how the direct effect of rhodomyrtone in the process of structural and physical cell changes that occur in bacteria (Traithan et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The minimum inhibitory and minimum bactericidal concentrations of rhodomyrtone were previously reported to be 0.5/0.5 µg/mL for EMRSA-16 and 0.5/1 µg/mL for S. aureus ATCC 29213 [ 23 ]. The antibacterial activities of rhodomyrtone have previously been demonstrated against several Gram-positive bacterial isolates, including S. aureus and S. epidermidis (MIC = 0.25–2 µg/mL) [ 24 ], Propionibacterium acnes (MIC = 0.12–0.5 µg/mL) [ 25 ], Streptococcus pneumoniae (MIC = 0.125–1 µg/mL) [ 26 ], S. aureus (MIC = 1.83 µg/mL) [ 27 ], Streptococcus suis (MIC = 0.5 µg/mL) [ 28 ], and Clostridium difficile (MIC = 0.625–2.5 µg/mL) [ 19 ]. The antibacterial activity of rhodomyrtone against P. acnes was reported to be comparable with that of the standard antibiotic erythromycin [ 25 ], and with that of vancomycin for S. aureus, and C. difficile [ 19 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that rhodomyrtone is a membrane-active compound [ 29 ]. The interaction of rhodomyrtone with the bacterial cell wall and membrane resulted in membrane invagination, which has been demonstrated as possible mechanism of rhodomyrtone mediated membrane distortion [ 21 , 28 ]. The presence of rhodomyrtone in cytoplasmic extracts might be due to the capability of rhodomyrtone to penetrate the cytoplasm of the cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation